A Jurisprudential and Legal Analysis of the Status of the COVID-19 Pandemic in Contract Law: A Critical Review of Judicial Precedent - Seyyed Hossein Tahami; Sayyed Mohammad Mahdi Qabuli Dorafshan; محسنی Mohseni; Azam Ansari (آموزه‌‌های فقه مدني, 2024)
The outbreak of the COVID-19 pandemic affected the performance of certain contractual obligations, thereby presenting a new challenge for legal practitioners, particularly judges, in resolving the resulting disputes. In this regard, it is essential to address the fundamental question of whether a pandemic can be considered an external factor (causes) affecting contracts. And secondly, how and to what extent does it affect the performance of contractual obligations, as well as the status of contracts impacted by the outbreak? The present study employs a descriptive-analytical research method to address the aforementioned questions. It seeks to provide a general theory by examining judicial precedents concerning these questions and by inductively analyzing specific instances mentioned in legal texts regarding the impact of external factors on the execution of contracts and their classification. This theory aims to not only elucidate the legal nature of the COVID-19 pandemic and its impact on contracts but also to be applicable to other emerging events. The results of the research indicate that events such as the COVID-19 pandemic can be identified as an external cause. The impact of the aforementioned diseases varies depending on whether they lead to the “nullification of the contract’s subject matter” or the “impossibility of favorable attaining of the contract’s subject matter.” Depending on the case, this may result in situations such as the automatic cancellation of the contract (Arabic: إنْفِساخ, Romanized: ʾinfisākh), the right to revocation, and so forth.